Allergic contact dermatitis from sculptured acrylic nails: special presentation with an airborne pattern - Paula Maio; Rodrigo Carvalho; Cristina Amaro; Raquel Santos; Jorge Cardoso (PAGEPress Publications, 2012)
Methylmethacrylate was first reported in 1941 as a cause of contact dermatitis. Since then, occupational contact allergies to acrylates in dentistry, orthopedic surgery, printing industry and industry have been reported, but few reports are found in the literature as a consequence of the contact with sculptured artificial acrylic nails which are increasingly popular. We describe here 3 patients with contact allergy to acrylates in artificial sculptured nails. Patch tests were performed with the Portuguese baseline series of contact allergens and an extended series of acrylates were applied. In particular, we tested three female patients with allergic contact dermatitis from sculptured acrylic nails. Two of these patients were both customers and also technical nail beauticians. Two patients developed periungual eczema; one presented only with face and eyelid dermatitis had no other lesions. The tests showed positive reaction to 2-hydroxyethylmethacrylate (2-HEMA) and 2-hydroxypropylmethacrylate (2-HPMA) in all the three patients. Our cases demonstrate the variety of clinical presentations of allergic contact dermatitis from acrylic sculptured nails. They show the need to warn patients of persistent and sometimes permanent side effects of these products. They also emphasize the importance of cosmetic ingredient labeling.